Pathogenetic mechanism of stented coronary arteries restenosis and the role of vasculoendothelial growth factor A - M.P. Kopytsya; I.M. Kutya; I.R. Vyshnevska (Кардіохірургія та інтервенційна кардіологія)
The contemporary issue of in-stent restenosis is reviewed in the article. The widespread use of interventional technologies for the treatment of acute and chronic forms of ischemic heart disease led to the appearance of the problem of coronary artery restenosis at the implantation site. The problem was apparently solved through introduction of drug-eluting stents instead of bare-metal stents. However, these stents also led to restenosis, but in more remote period. The issue of the contemporary cardiology is how to avoid this complication. Risk stratification of restenosis development in various groups of patients is a main task today, as the treatment of this condition is not simple. The article analyzes data of the studies conducted up to date. It studies the pathogenetic mechanisms that would develop restenosis of the previously stented coronary arteries (in various stents) and factors contributing to the formation of restenosis. The results of the studies show that vasculoendothelial growth factor-A (VEFR-A) plays a role in the development of restenosis and might predict the formation of this complication. The review addresses the issues of different genotypes of VEFR-A, which may predispose to the formation of stent restenosis.